2024
DOI: 10.1007/s12020-024-03718-2
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid disorders induced by immune checkpoint inhibitors

Dimitra Karaviti,
Eleni-Rafaela Kani,
Eleftheria Karaviti
et al.

Abstract: Immune checkpoint inhibitors (ICIs) are a revolutionary class of drugs that powerfully contribute to cancer therapy by harnessing the immune system to fight malignancies. However, their successful use as anti-cancer drugs is accompanied by a wide spectrum of immune-related adverse effects (irAEs), including endocrinopathies. Among them, thyroid dysfunction stands out as one of the most common endocrinopathies induced by ICI therapy and surfaces as a prominent concern. Destructive thyroiditis is the pathophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Hypothyroidism is one of the most common endocrine diseases in ICIs therapy, usually occur within 3 weeks to 10 months after the start of ICIs treatment. Studies have indicated that the incidence of hypothyroidism when using PD-1 inhibitors alone ranges from 3.9% to 8.5%, while it increases to 10.2% to 16.4% with combination ICIs therapy ( 59 ). It is important to note that our patient did not experience any severe immune-related adverse reactions aside from hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism is one of the most common endocrine diseases in ICIs therapy, usually occur within 3 weeks to 10 months after the start of ICIs treatment. Studies have indicated that the incidence of hypothyroidism when using PD-1 inhibitors alone ranges from 3.9% to 8.5%, while it increases to 10.2% to 16.4% with combination ICIs therapy ( 59 ). It is important to note that our patient did not experience any severe immune-related adverse reactions aside from hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%